0455 Determinants of Hypercapnia in Obesity Hypoventilation Syndrome with Obstructive Sleep Apnea. (27th April 2018) - Sirijanchune, P; Kaw, R; Wang, L; Herbert, M; Mehra, R; Aboussouan, L S
Abstract: Introduction: In patients with obstructive sleep apnea (OSA) but without obesity hypoventilation (OHS), longer sleep-disordered breathing (SDB) events relative to the inter-event duration may initiate elevation of PaCO2 . However, we hypothesized that metabolic and mechanical factors may be responsible for the progression to OHS, and may explain why more individuals with obesity or OSA do not develop OHS. We therefore sought to determine the role of SDB, metabolic and mechanical factors variables mechanical factors to the severity of daytime hypercapnia in patients with OHS. Methods: This retrospective cross-sectional single center study included 80 patients, aged > 18 years, with OSA, BMI > 30 kg/m 2 and wake PaCO2 ≥ 45 mmHg, identified through an electronic medical records data base of patients with unrecognized OHS undergoing non-elective cardiac surgery. Univariate and multiple linear regression analyses were used to assess the association of wake PaCO2 with SDB variables (apnea hypopnea index, apnea and hypopnea event duration, inter-event duration), metabolic (HCO3, body surface area, metabolic syndrome, fasting blood glucose[FBG]) and mechanical factors (body mass index [BMI], forced vital capacity [FVC], forced expiratory volume in 1 second [FEV1 ]). Results: The median [interquartile range] PaCO2 was 49.0[47.0, 54.4]. In a univariable linear regression analysis the PaCO2, was positively correlated with HCO3 (Beta-coefficient 0.59; 95%CI, 0.26–0.91; P <0.001), BMI (Beta-coefficient 0.21; 95%CI, 0.04–0.35; P =0.015) and FBG (Beta-coefficient 0.03; 95%CI, 0.01–0.05; P =0.014), and negatively with the mean nocturnal SaO2 (Beta-coefficient t -0.42; 95%CI, -0.70–0.15; P =0.003). Patients with the metabolic syndrome had a higher PaCO2 than those without (52.1 ± 0.9 vs. 48.9 ± 1.3, P =0.046). In multivariate analysis, the HCO3, fasting glucose, and mean nocturnal SaO2 remained significant predictors of the PaCO2 . Conclusion: Metabolic factors (bicarbonate level, fasting blood glucose, metabolic syndrome), as well as mechanical factors (BMI) are more important determinants of hypercapnia in OHS than sleep disordered breathing variables (including AHI, event and interevent duration). In a multivariable model, metabolic factors and the mean nocturnal SaO2 remain significant predictors. We conclude that the progression to OHS in OSA is predominantly due to mechanical and metabolic factors. Support (If Any):